Analisis Sistem Pemberian Kredit dan Penagihan Piutang Pada PT. Bank Sumut Kantor Cabang Pulo Brayan Medan - Halawa, Oktoberlina; Aisyah, Siti (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the credit granting system and receivables collection at PT. Bank Sumut, Pulo Brayan Medan Branch Office. The research method used was descriptive qualitative with data collected through interviews, observations, and documentation studies. The findings indicate that the credit granting system at Bank Sumut has been carried out based on the prudential principle by applying the 5C analysis (Character, Capacity, Capital, Collateral, and Condition of Economy) to minimize the risk of non-performing loans. In terms of receivables collection, the bank implements a gradual approach, starting with persuasive communication, warning letters, direct visits, and loan restructuring for debtors facing difficulties. Legal action is pursued only as a last resort. The challenges encountered include delays in debtor financial information, lack of debtor’s good faith, and external factors such as economic conditions. This research is expected to contribute to the development of risk management strategies in banking, particularly in credit granting and receivables collection.